A comparative study of Johann Sebastian Bach's Courante movement in the English suites and the French suites / Nurul Ain Syazwani A Rahman - A Rahman, Nurul Ain Syazwani (2019)
The Courante movement is found in the Bach's English suites and French suites. By studying details the differences it may help students to interpret the pieces better. . In this case, it will help a lot of students on how to tackle this problem while playing Bach's suite. This research will be looking at three main objectives, which is to show that comparative study of Johann Sebastian Bach's Courante movement between English suite and French suite is really important. Firstly, to analyse the differences for the Courante movement between the English suites and French suites. Next, to investigate the influences of Baroque Dance towards the performance for Courante movement in English suite and French suite, then, to justify the interpretation of articulations in the pieces that can affect the performances. This study will be useful for piano students who are playing Bach's suite for Courante movement.